Regional circuits of international medical travel: Prescriptions of trust, cultural affinity and history - Whittaker, Andrea; Chee, Heng Leng; Por, Heong Hong (Wiley, 2017)
Intra-regional medical travel by patients from Indonesia to Penang in Malaysia is embedded in and facilitated by regional circuits. Although such movement is fuelled by dissatisfaction with the health-care services offered in Indonesia, we argue that these contemporary movements for health care are also a continuation of existing exchanges for trade, education and cultural ties that have long existed. In the first part of the paper, we consider the historical interconnections between the locations of Medan and Aceh in Indonesia and Penang in Malaysia. Based upon fieldwork and interviews with 70 intra-regional patients travelling to Penang for treatment, we describe how these interconnections are now manifested in travel for medical care. We argue that the temporary exit from the Indonesian health system to pursue care in hospitals in Penang by some Chinese Indonesians and Acehnese follows patterns and logics based on social histories of discrimination and conflict as well as geographical convenience. This highlights the need to contextualise such travel not just as geographic movements across space but also through the depth of time and local histories.